Biodegradable Elastic Sponge from Nanofibrous Biphasic Calcium Phosphate Ceramic as an Advanced Material for Regenerative Medicine. (9th July 2021) - Zhang, Yonggang; Li, Jiaping; Soleimani, Mohammad; Giacomini, Francesca; Friedrich, Heiner; Truckenmüller, Roman; Habibovic, Pamela
Abstract: Biodegradable porous calcium phosphate (CaP) ceramics are widely used as synthetic graft substitutes for bone regeneration, owing to their chemical and structural similarity to bone and associated bioactivity in terms of bone‐bonding, osteoconductive, and even osteoinductive properties. Nevertheless, the intrinsic brittleness and poor processability of porous CaP ceramics strongly impair their clinical applicability. Herein, a biphasic calcium phosphate (BCP) sponge is developed that consists of a self‐supporting network of seamlessly interwoven hydroxyapatite nanowires and β‐tricalcium phosphate nanofibers and possesses a highly interconnected porous structure with open cell geometry and ultrahigh porosity. Owing to its unique properties, the ceramic sponge can be easily processed into various shapes and dimensions, such as cylindrical scaffolds and thin, flexible membranes. Moreover, the BCP sponge can be introduced into a bone defect in a compacted or folded state from a syringe and, upon wetting, expand to its original shape, thereby filling the cavity. The nanofibrous sponge gradually degrades in vitro and rapidly mineralizes when immersed in simulated body fluid. Moreover, it adsorbs significantly more proteins than a conventional porous BCP ceramic. Finally, the nanofibrous sponge supports the attachment, proliferation, and osteogenic differentiation of human mesenchymal stromal cells comparable to the conventional porous BCP ceramic. Abstract : An inorganic, biodegradable, nanofibrous biphasic calcium phosphate ceramic sponge is developed with ultrahigh and hierarchical porosity, elasticity and flexibility, shape‐memory ability, and excellent processability. The sponge serves as a synthetic extracellular matrix for protein adsorption, human mesenchymal stromal cells proliferation, and osteogenic differentiation. This material extends the applicability of calcium phosphate‐based bone grafts in bone regeneration and related clinical applications.